Free-fall drop test with interchangeable surfaces to recreate concussive ice hockey head impacts - Haid, D.; Duncan, O.; Hart, J.; Foster, L. (Sports Engineering, 2023)
Ice hockey has one of the highest concussion rates in sport. During collisions with other players, helmets offer limited protection. Various test protocols exist often requiring various types of laboratory equipment. A simplified test protocol was developed to facilitate testing by more researchers, and modifications to certification standards. Measured kinematics (acceleration vs. time trace shape, peak accelerations, and impact duration) of a Hybrid III headform dropped onto different surfaces were compared to published laboratory representations of concussive impacts. An exemplary comparison of five different helmets, ranging from low (US$50) to high cost (US$300), covering a range of helmet and liner designs, was also undertaken. Different impact conditions were created by changing the impact surface (Modular Elastomer Programmer pad, or 24 to 96 mm of EVAZOTE-50 foam with a Young's modulus of ~ 1 MPa), surface orientation (0 or 45°), impact site, and helmet make/model. With increasing impact surface compliance, peak accelerations decreased and impact duration increased. Impacts onto a 45° anvil covered with 48 mm of foam produced a similar response to reference concussive collisions in ice hockey. Specifically, these impacts gave similar acceleration vs. time trace shapes, while normalized pairwise differences between reference and measured peak acceleration and impact duration, were less than 10% (difference/maximum value), and mean (± SD) of accelerations and duration fell within the interquartile range of the reference data. These results suggest that by modifying the impact surface, a free-fall drop test can produce a kinematic response in a helmeted headform similar to the method currently used to replicate ice hockey collisions. A wider range of impact scenarios, i.e., fall onto different surfaces, can also be replicated. This test protocol for ice hockey helmets could facilitate simplified testing in certification standards and research.